2023
DOI: 10.30595/juita.v11i1.15457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bicluster Analysis Results in Capture Fisheries Using the BCBimax Algorithm

Abstract: Biclustering is a simultaneous clustering technique by finding sub-matrixes that have the same similarity between rows and columns. One of the biclustering algorithms that is relatively fast and can be used as a reference for the comparison of several algorithms is the BCBimax algorithm. The BCBimax algorithm works by finding a sub-matrix containing element 1 of the formed binary data matrix. The selection of thresholds in the binarization process and the minimum combination of rows and columns are essential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Secondly, it is based on the smallest AvMSR value. Furthermore, another important consideration is how the information obtained from the biclustering results (Wulandari et al, 2023), in other words the model can produce more than one bicluster (๐ต๐ถ > 1). Based on Table 3, it can be shown that models 1 and 3 have ๐‘Ÿ value less than 1 (๐‘Ÿ < 1).…”
mentioning
confidence: 99%
“…Secondly, it is based on the smallest AvMSR value. Furthermore, another important consideration is how the information obtained from the biclustering results (Wulandari et al, 2023), in other words the model can produce more than one bicluster (๐ต๐ถ > 1). Based on Table 3, it can be shown that models 1 and 3 have ๐‘Ÿ value less than 1 (๐‘Ÿ < 1).…”
mentioning
confidence: 99%